MILKFISH BRACKISHWATER POND CULTIVATION: A CASE STUDY OF TAMBAK BANDENG IN “SUMBERSARI” - Nurdien H Kistanto (JOURNAL OF COASTAL DEVELOPMENT, 2001)
Milkfish brackishwater pond (tambak bandeng) in “Sumbersari” can be divided into three types: (a) fry pond; (b) brackishwater pond type 1; and (c) brackishwater pond type 2. Milkfish brackishwater pond cultivation is profitable, especially when the area is large. The idea of cultivating giant tiger shrimp (udang bago) in the brackishwater pond by using a mixed (campuran) method appears to generate considerable additional income for those who practiced it.